2009
DOI: 10.1016/j.curtheres.2009.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sumatriptan on nitric oxide synthase enzyme production after iatrogenic inflammation in the brain stem of adolescent rats: A randomized, controlled, experimental study

Abstract: In this experimental model of migraine in adolescent rats, intracisternal injection of carrageenan was associated with a significant increase in the production of NOS enzymes in the brain stem. Pretreatment with sumatriptan was associated with a decrease in NOS production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The increased intracellular Ca + leads to activating nNOS . Previously, it was shown that sumatriptan inhibits NOS enzymes activity including nNOS . It suppresses the increase in NOS level induced by intracisternal carrageenan and the activity of NOS in guinea‐pig cerebral blood vessels .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased intracellular Ca + leads to activating nNOS . Previously, it was shown that sumatriptan inhibits NOS enzymes activity including nNOS . It suppresses the increase in NOS level induced by intracisternal carrageenan and the activity of NOS in guinea‐pig cerebral blood vessels .…”
Section: Discussionmentioning
confidence: 99%
“…The 5‐HTR1b/1d are expressed on primary sensory nerves as well as various population of skin cells . There are studies reported that 5‐HTR1 agonists inhibit NOS activity to suppress pain signals . Despite the known role of 5‐HTR1b/1d agonists in pain, limited studies have investigated their involvement in itch.…”
Section: Introductionmentioning
confidence: 99%
“…Periorbital, hind-paw, and jaw-pressure thresholds were determined by applying von Frey monofilaments (Stoelting Co., Wood Dale, IL, USA). Each monofilament is identified by manufacturer-assigned force values (26,15,10,8,6,4, 2, 1.4, 1, 0.6, 0.4, 0.07 g). The von Frey hairs are calibrated nylon monofilaments that generate a reproducible buckling stress.…”
Section: Methodsmentioning
confidence: 99%
“…Most headache models modify an animal to mimic migraine symptoms 2‐7 . This usually requires significant manipulation of the animal, ie, craniotomy with electrical or chemical stimulation of the dura 8‐13 . Many of these models are probably models of secondary headache 14 .…”
mentioning
confidence: 99%
See 1 more Smart Citation